Can You See What I See, Mata sebagai Objek Penciptaan Seni Fotografi Ekspresi - Handry Rochmad Dwi Happy; Elfa Olivia Verdiana (Jurnal Kajian Seni, 2017)
The human eye holds a beauty potential that is rarely seen. In contrast to the eyes of animals such as insects and reptiles that are almost the same in the preparation and shape, the human eyes are composed of a different variety of patterns and textures even right and left eye on each person. In this paper, the photographs are presented using the conceptual techniques of macro photography and photographic expression. By using macro photography techniques that can magnify an object and capture the details of the beauty of the human eye, it can be seen clearly. The creation process concist ofexploration, experimentation, and formation. Taking picture was done by using DSLR camera and helped by the lighting from studio. Selection of the human eye as an object in photography using macro technique is a new thing. The results obtained in each image capture raise an unexpected impression.